Antibacterial Activity of Cinnamomum burmannii Extract Against Escherichia coli - Febrina Rosa Winda; Suparno Suparno; Zuhdan Kun Prasetyo (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the antibacterial activity of the cinnamon extract in inhibiting the growth of Escherichia coli. The research design was a laboratory experiment consisting of three phases, namely the preparation phase of cinnamon extract using the maceration method using 96% ethanol, the characterization phase consisting of qualitative analysis with phytochemical tests and quantitative analysis with UV-Vis spectrophotometry, and the application phase including antibacterial activity test by disc diffusion method (Kirby-Bauer Test). The concentration series were 20%, 40%, 60%, 80%, and 100%, chloramphenicol as the positive control and methanol as the negative control. The results showed that cinnamon extract positively contained flavonoids with a total content of 1.310 mg QE/g or 0.131%. Cinnamon extract is effective as an antibacterial in the medium category with the optimum concentration to inhibit Escherichia coli is 40% indicated by the diameter of the inhibition zone of 9.55 mm at 12 hours of incubation. Therefore, the cinnamon extract has potential activity against Escherichia coli.